O louco trabalhando em um modelo de autogestão desvinculado dos serviços de saúde - Marcos Paulo do Espírito Santo (2021)
Under the influence of the Brazilian Psychiatric Reform and the Anti-Asylum Movement, a partnership between movements Mental Health and Solidarity Economy was fostered in the 2000s aiming at the psychosocial rehabilitation of people with mental suffering through work. Initially, supervised work spaces were created within the Psychosocial Care Network (RAPS). However, today there are already enterprises that are disconnected from health services and organized on the basis of self-management. In view of this fissure, the present dissertation aims to observe the changes caused in the lives of people with mental suffering who work in such self-managed enterprises. First, we describe how this change occurred in the historical relationship between work and madness. Then, having the Suricato Association as the unit of analysis, we conducted participant observations and semi-structured interviews with associates and ex-associates. As a result, we noted some points from which we approach the experience of these people as a kind of moral anti-career for people who have mental suffering: I) greater possibilities of socialization in relation to the tutored spaces; II) internalization of social identities beyond madness; and III) modification in the sense of work. Finally, dilemmas and tensions were also observed, especially the shadow of guardianship and the issue of income generation.